Feasibility of Remote Monitoring to Confirm Exercise Adherence in High Risk Pregnant Women [15N]. (May 2020) - Kogutt, Benjamin K.; Sheffield, Jeanne S.
Abstract : INTRODUCTION: Pregnancy is an ideal opportunity for women to focus on physical health; however, exercise recommendations are rarely met. At-home fitness is more accessible than ever due to technology-based interventions, and with the addition of wearable technology, real-time adherence and intensity feedback is possible. The objective of our study is to determine if contemporaneous, mobile technology can provide an innovative method to monitor exercise in a high-risk pregnant population remotely. METHODS: This is a prospective, randomized controlled pilot study with two arms: exercise vs. standard counseling. Exercise was logged and tracked remotely in both groups. Once an exercise session was recorded, participation was confirmed by cross-referencing participant's FitBit activity and heart rate monitor (San Francisco, CA), thus providing a method to confirm participation and monitor degree of exercise intensity. RESULTS: Sixteen total patients were enrolled, eight in each arm. 102 exercise sessions were logged: 80 (78%) in the intervention group vs. 22 (22%) in the non. Exercise was confirmed in 79 of the 102 exercise sessions (77%). Interestingly, only 18% of recorded sessions reached moderate intensity based on heart rate parameters, and none reached vigorous intensity. CONCLUSION: Connected health technologies can provide a reliable, cost effective, and efficient method to determine adherence to and degree of exercise intensity in a high-risk pregnant population. Providing feedback to patients about their actual vs. perceived exercise intensity may improve the efficacy of their regimens. Additional research is needed to determine which methods are most effective to motivate exercise in pregnancy.